2011
DOI: 10.3989/scimar.2011.75n3559
|View full text |Cite
|
Sign up to set email alerts
|

The response of meiofauna to human trampling on coral reefs

Abstract: Coastal environments are trampled by humans worldwide; however, there are few studies that evaluate the effect of trampling on the meiofauna of hard substrates, and none on meiofauna of reef environments. We investigated the effects of trampling due to tourism on the meiofauna of reef formations on the northeastern coast of Brazil. Samples were taken from five paired stations located in two areas on the reef: an area protected since 2004, and an area open to tourist visits. Trampling caused important changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
7
1
4
Order By: Relevance
“…Some studies showed the negative effect of trampling on reef communities (Liddle and Kay 1987, Neil 1990, Hawkins and Roberts 1994, Brown and Taylor 1999, Rodgers and Cox 2003, Sarmento et al 2011. In the present study, the growth rate of P. caribaeorum in Porto de Galinhas did not differ between visited and unvisited areas, not corroborating our initial hypothesis.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Some studies showed the negative effect of trampling on reef communities (Liddle and Kay 1987, Neil 1990, Hawkins and Roberts 1994, Brown and Taylor 1999, Rodgers and Cox 2003, Sarmento et al 2011. In the present study, the growth rate of P. caribaeorum in Porto de Galinhas did not differ between visited and unvisited areas, not corroborating our initial hypothesis.…”
Section: Discussioncontrasting
confidence: 62%
“…Conversely, the reef of Porto de Galinhas has an extension of 900 m and is close to the beach line, within easy access, which makes this beach one 987 GROWTH OF Palythoa caribaeorum IN BRAZILIAN REEFS of the most visited in the Brazilian coast. Annually, Porto de Galinhas receives approximately 65,000 tourists (Sarmento et al 2011). The reef is divided in two sectors by a channel with approximately 8 m in depth.…”
Section: Study Areamentioning
confidence: 99%
“…The depth of the reef structures rarely exceeds 10 m (Laborel, 1970;Dominguez et al, 1990;Maida and Ferreira, 1997). Similarly to reefs elsewhere, in Brazil these habitat is subject to intense anthropogenic pressure, aggravated by their proximity to shore (Castro and Pires, 2001;Feitosa et al, 2002;Fernandes et al, 2005;Barradas et al, 2010;Sarmento et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Oigman-Pszczol and Creed (2011) showed the drastic consequences for subtidal corals and macroalgae derived from recreational boat traffic and the inputs of solid and liquid waste at the subtropical beach of Búzios (Rio de Janeiro State). Furthermore, trampling has been shown to affect meiofaunal communities on the reef tops of Porto de Galinhas, Pernambuco State (Sarmento et al 2011;Sarmento and Santos 2012).…”
Section: Introductionmentioning
confidence: 97%